2014
DOI: 10.1021/ja510081r
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomerically Enriched Tris(boronates): Readily Accessible Conjunctive Reagents for Asymmetric Synthesis

Abstract: The catalytic enantioselective diboration of vinyl boronate esters furnishes chiral tris(boronates) in a selective fashion. Subsequent deborylative alkylation occurs in a diastereoselective fashion, both for intermolecular and intermolecular processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
72
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(74 citation statements)
references
References 58 publications
0
72
0
2
Order By: Relevance
“…Accordingly, its use with 1,1-diborylalkenes could proceed via intermediacy of a stabilized α -borylcobalt intermediate. 35 As shown in Scheme 8, sequential 1,1-diboration-hydroboration of terminal alkynes involving ( Cy APDI)CoCH 3 ( 1 ) and (Terpy)Co(CH 2 SiMe 3 ) ( 14 ) 34 furnished a collection of 1,1,1-triboronates 19 in 50–76% yield over two steps. Importantly, carbonyl-based functional groups were compatible with this hydroboration protocol, as evidenced by the synthesis of triboronates 19e , 19i , and 19g .…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, its use with 1,1-diborylalkenes could proceed via intermediacy of a stabilized α -borylcobalt intermediate. 35 As shown in Scheme 8, sequential 1,1-diboration-hydroboration of terminal alkynes involving ( Cy APDI)CoCH 3 ( 1 ) and (Terpy)Co(CH 2 SiMe 3 ) ( 14 ) 34 furnished a collection of 1,1,1-triboronates 19 in 50–76% yield over two steps. Importantly, carbonyl-based functional groups were compatible with this hydroboration protocol, as evidenced by the synthesis of triboronates 19e , 19i , and 19g .…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] We hypothesised that an alternative route to induce intramolecular 1,2-boryl-anion migration would be the activation of an unsaturated R À group (e.g. [19][20][21][22] Thes elective (for intramolecular 1,2-boryl migration) activation of [(vinyl)B 2 Pin 2 ] À (complex B,Scheme 1, bottom), requires judicious choice of the borane,B R 3 ,a sarange of outcomes are feasible,i ncluding:i )vinyl-anion transfer from B to BR 3 ;i i) binding of BR 3 to an oxygen atom in B and subsequent CÀOorB ÀOcleavage;iii){BPin} À anion transfer from B to BR 3 ;i v) BR 3 activation of the vinyl p system and intramolecular {BPin} À transfer.W hile (i)a nd (ii)a re undesirable,p athway (iii)w ould be an attractive route to unsymmetrical diboranes using commercial Grignard reagents as activators.E qually notable and our primary focus,i ntramolecular 1,2-boryl migration (pathway (iv)) would be anew and simple route to 1,1,2-triborylated alkanes. This approach is attractive as it avoids prefunctionalization of the carbanion activator.I ti sc onceptually related to the Zweifel reaction, [18] but the use of borane Lewis acids and {BPin} À as the migrating group will lead to differentially functionalised 1,1,2-triborylated alkanes in one step.Related 1,1-diborylated alkanes have emerged as highly versatile reagents used in selective CÀCb ond formation by the Suzuki-Miyaura coupling reaction or by deprotonation/ deborylation of the diborylated carbon atom.…”
mentioning
confidence: 99%
“…[2] However,ifone could create stereogenic centers in acyclic systems,not through aclassical S N 2reaction between ac hiral electrophile and an achiral nucleophile (Scheme 1, path A), but rather through the reaction of ac hiral nucleophile (that would be used as an ew chiral building block for stereoselective synthesis) with an achiral electrophile,i tw ould broaden the synthetic possibilities in organic synthesis (Scheme 1, path B). [4,5] More recent developments have shown that few main-group organometallic species,s uch as organomagnesium [6] and organolithium, [7] as well as transition-metal species,s uch as alkylcopper [8] and alkylzinc, [9] present some configurational stability under particular circumstances (Scheme 1, path C). [3] To fulfill the requirements of configurational stability for secondary carbanions (R 1 ¼ 6 R 2 = alkyl, A)m etalloids such as organoboronates were intensively investigated.…”
mentioning
confidence: 99%